2021
DOI: 10.1049/smc2.12011
|View full text |Cite
|
Sign up to set email alerts
|

Spatial demand forecasting based on smart meter data for improving local energy self‐sufficiency in smart cities

Abstract: The use of distributed energy resources (DERs) in a city contributes to the net zero CO2 of a city. However, the spatially uneven distribution of power demand and surplus electricity causes congestion in the grid system, making wide‐area operation difficult. The concept of local energy self‐sufficiency via energy management, in which batteries or electric vehicles are charged using power generated by DERs and discharged to neighbouring consumers, is expected to be a way to avoid grid conjunction while maximizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Other authors like McLoughlin et al (2015), Khan et al (2018) or Haben et al (2016 use smart meter data for characterizing residential customers according to their daily energy usage patterns utilizing clustering techniques. In Miyasawa et al (2021), the smart meter data of a major city is used for forecasting the spatial demand in the next hours.…”
Section: Related Workmentioning
confidence: 99%
“…Other authors like McLoughlin et al (2015), Khan et al (2018) or Haben et al (2016 use smart meter data for characterizing residential customers according to their daily energy usage patterns utilizing clustering techniques. In Miyasawa et al (2021), the smart meter data of a major city is used for forecasting the spatial demand in the next hours.…”
Section: Related Workmentioning
confidence: 99%
“…Conversely, information on power demand and generation for minutes or hours ahead predicted for each building helps to control power equipment, plan the operation of generated power, and optimise the energy use in all buildings, for energy management [20][21][22]. For efficient energy management and a stable power supply through a power grid, hourly or perminute power grid forecast results play key roles, because consideration of the time-series balance between generation and demand is necessary [21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Short term ahead (hourly or per minute) One or some buildings Energy management in houses or buildings [20] A city Regional energy management for local self-sufficiency (Target of this study) [21,22] Power grid Stabilisation of the power system [23] Long term ahead (monthly or yearly) One or some buildings Determination of equipment configuration [24,25] A city Estimation potential of additional PV installation [16,19] Power grid Investment decisions in power grid and generation facilities [26][27][28] incorporate multiple heterogeneous features from a smart grid that exploits sensing and information communication technologies for demand forecasting. Conventionally, demand data in cities were measured monthly for billing by power companies, and no mechanism for collecting the spatio-temporal power demand existed; therefore, they have proposed the installation of additional sensors in the power grid.…”
Section: Relevant Workmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Miyasawa et al (2021), local energy self-sufficiency is achieved by combining the data reported by smart meters with distributed energy, which greatly reduces the operating difficulties of wide-area power grids. Aiming at the optimization of battery energy storage capacity, a charging and discharging strategy based on cost and time of use price was proposed, and an optimization model aimed at maximizing revenue was established.…”
Section: Distributed Energy Accessmentioning
confidence: 99%